Human-machine Integration: Current Trend of AI and Journalism in Asia - Yogie Alwaton; Rana Akbari Fitriawan; Oki Achmad Ismail (Jurnal Riset Jurnalistik dan Media Digital, 2025)
Abstract. The use of AI in newsrooms has transformed journalistic practices, through human-machine integration. This phenomenon has been widely studied in European and African countries. However, in Asia, although some countries such as China have adopted AI technology in their journalism, similar research is still limited. This article aims to map the current trends in the use of AI in journalism in Asia, examine the challenges faced by newsrooms, and the potential replacement of the journalist profession by AI. Using a Systematic Literature Review, this article suggests that the current use of AI in Asia has occurred in only a few countries. This study also found that data bias and privacy violations are challenges for newsrooms in Asia. Finally, this study shows that (AI) will not replace human journalists. Journalists do not need to be afraid that AI will replace their profession. This article contributes to filling the research gap on AI and journalism in Asia, and provides relevant insights for academics, media practitioners, and policymakers in preparing adaptive strategies to technological developments.